WEBSITE GOES INTO CLASSROOM: MATERIALS DEVELOPMENT USING AN AUTHORING TOOL ‘LESSON WRITER’ - Gusti Astika (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
With the development of Information and Computer Technology (ICT), life in the 21st century has provided us with easy access to print as well as digital information. This development has brought about challenges to education system in general. In language education the challenges have to be responded with innovative ways to teach and learn languages. In ELT, especially in an EFL context such as that in Indonesia, English teachers must be able to acquire and possess a range of skills to utilize information, media, and education technology in teaching. One educational tool that can be used is an authoring software called Lesson Writer. This tool can be used to create lessons to develop the four language skills integratively using authentic texts about current world news on   education, economy, health, etc. with audio and/or video files accessible through   internet websites such as the Voice of America.com. This presentation will begin with a brief discussion about using technology in language teaching, then, follows an introduction of Lesson Writer and  step by step procedure to use its facilities to create exercises for language and skills development. By the end of the presentation, the participants are introduced with a model lesson created with Lesson Writer.